Industries want work-ready graduates - Ruhil Amal, Azmuddin; Wan Jumani, Fauzi (2022)
7 February 2022 - Industry Advisory Panel (IAP) comprising of Mr Mohd Yusrizal Mohd Yusoof (Mercedes-Benz Malaysia), Mdm Farah Hani (DRB Hicom), Mr Mohd Najib Ibrahim (Cyberview Sdn Bhd), Mr Mohd Hazaruddin Muhammad (BASF Petronas Chemicals) and Mr Mohd Nizam Yaacob (Mercedes-Benz Malaysia) all gave very insightful feedback to industry current issues and needs related to local fresh graduates in the recent IAP meeting with the Centre for Modern Languages (CML), Universiti Malaysia Pahang (UMP) that was conducted via Microsoft Teams platform.